Revitalization of the story of Asal Mula Pulut as teaching material for Indonesian language for foreigners - Dian Syahfitri; Gleddeanaria Sypriana Naibaho; Grace Alviyano Sigiro (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2026)
This study examines the revitalization of the traditional narrative regarding Asal Mula Pulut as an educational resource for Indonesian Language for Foreign Speakers (BIPA). The reason for this research stems from the necessity to safeguard local oral traditions and incorporate Indonesian cultural heritage into language education. In many Indonesian communities, pulut stands for unity, thankfulness, and fertility. This makes its origin story a culturally rich way to teach people from different cultures. As part of the revitalization process, the story is turned into a comic called Asal Mula Pulut. This comic is meant to teach BIPA students about cultural values through pictures and words that are easy for them to understand. This research employs a qualitative descriptive approach, incorporating ethnographic documentation and textual analysis. Data were collected from oral and written folklore, analyzed for linguistic characteristics and cultural significance, and subsequently converted into pedagogically suitable comic content. The results showed that the Pulut story has words, moral lessons, and cultural ideas that help middle BIPA students learn new words and understand what they read. This adaptation of the comic effectively connects traditional knowledge with modern learning tools, which makes students more interested and aware of other cultures.